Clinical features of development of chronic cerebral ischemia against background of pronounced decrease of cognitive functions. - Yu. D. Zalisna (Medičnì Perspektivi, 2013)
The paper presents the results of analyses of cognitive failure in chronic cerebral ischemia (CCI) with lesion of deep divisions of the brain white matter and basal ganglia, leading to disruption of communication of frontal and subcortical brain structures (the phenomenon of separation). Mechanism of separation primarily is associated with hypertension, which leads to secondary changes of the vascular wall microvasculature. For cerebral vascular insufficiency and for diseases, primarily involving basal ganglia, intellectual inertia, bradyphreniya and decreased concentration are more common. According to studies, chronic cerebral ischemia (CCI) is recorded in 20-30% of people of working age. The main etiological forms of CCI are considered to be hypertensive, atherosclerotic and mixed. For CCI of the second stage formation of neurological syndromes (pseudobulbar, pyramidal, extrapyramidal, atactic), increased cognitive disorder that causes temporary or permanent disability of patients, reduction of their quality of life are characteristic. The aim of the study was to determine the characteristics of cognitive impairment in patients with CCI (hypertonic and mixed origin) and their relationship to clinical and neurological manifestations of the disease. Based on the data obtained through clinical examination and neuropsychological testing, marked processes of attention exhaustion and a higher risk of progression of cognitive impairment in the group with a mixed form (hypertension and atherosclerotic) were revealed.